Pengaruh Modernisasi Sistem Administrasi Perpajakan terhadap Kepatuhan Wajib Pajak (Survei atas Wajib Pajak Badan pada KPP Pratama Bandung â€Xâ€) - Sri Rahayu; Ita Salsalina Lingga (Universitas Kristen Maranatha, 2009)
The objective of this research is to examine whether modernization in taxation administration system at Bandung ”X” Tax Office affects tax compliance. Type of this research is quantitative descriptive. The sample size is determined with purposive sampling method. Survey method is applied with data collected through interview and questionnaire and multiple regression analysis and t-test are applied in data processing. The research shown that modernization in taxation administration system positively significant affects tax compliance. Keywords: modernization in taxation administration system, tax compliance.